2004
DOI: 10.1016/j.bbamcr.2004.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Cell adhesion receptors, tyrosine kinases and actin modulators: a complex three-way circuitry

Abstract: The interaction of cells with surrounding matrix and neighbouring cells governs many aspects of cell behaviour. Aside from transmitting signals from the external environment, adhesion receptors also receive signals from the cell interior. Here we review the interrelationship between adhesion receptors, tyrosine kinases (both growth factor receptor and non-receptor) and modulators of the actin cytoskeletal network. Deregulation of many aspects of these signalling pathways in cancer highlights the need for a bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 283 publications
3
110
0
2
Order By: Relevance
“…Accordingly, disruption of cell-cell junctions has been associated with the breakdown of cellular barriers and the initiation of EMT (33,34). Growth factors, cytokines, or oncogenes are physiological regulators of cadherin function because they induce intracellular signals that disrupt cell-cell junctions, promote actin reorganization, and induce a migratory phenotype (35). Previous studies have demonstrated that disruption of cell-cell junctions depends on intracellular kinases and/or phosphatases that regulate the phosphorylation state of cadherins and their cytosolic binding partners including ␣-, ␤-, ␥-, and p120-catenin (6,10,18,19,23).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, disruption of cell-cell junctions has been associated with the breakdown of cellular barriers and the initiation of EMT (33,34). Growth factors, cytokines, or oncogenes are physiological regulators of cadherin function because they induce intracellular signals that disrupt cell-cell junctions, promote actin reorganization, and induce a migratory phenotype (35). Previous studies have demonstrated that disruption of cell-cell junctions depends on intracellular kinases and/or phosphatases that regulate the phosphorylation state of cadherins and their cytosolic binding partners including ␣-, ␤-, ␥-, and p120-catenin (6,10,18,19,23).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, co-expression of Fyn had no effect on the CAP4-flotillin interaction and vice versa, suggesting biochemically that these three proteins may be able to co-exist in the same complex. Fyn and other Src family kinases are well known regulators of integrin signaling and the actin cytoskeleton (39). Additionally, the role of Src kinases in insulin receptor signal transduction is well documented (37,40,41).…”
Section: Figmentioning
confidence: 99%
“…Literature data have indicated that Src kinases can act in concert with Syk kinase to participate in membrane receptor complexes, which among others contain RTKs (38). SmVKR1 of S. mansoni is an RTK and was shown to be expressed in the ovary of females (23), thus co-localizing with SmTK6 and SmTK4 (13,17).…”
Section: Journal Of Biological Chemistry 42329mentioning
confidence: 99%